MENINGKATKAN HASIL BELAJAR IPA KONSEP SISTEM PENCERNAAN MELALUI PEMBELAJARAN SCIENCE-EDUTAINMENT BERBANTUAN MEDIA ANIMASI - Azizi, Asrorul; Muttaqin, Muh. Zaini Hasanul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
This classroom action research aims to improve students learning outcomes on the concept of light. The subjects of this study were students of class VIIIB of SMP Negeri 3 Praya for the academic year 2021/2022, totaling 33 people. This research was conducted in 2 cycles. Each cycle consists of stages of planning, implementing actions, observing, evaluating and analyzing and reflecting. Based on the results of the research, it can be concluded that the application of animation-assisted science-edutainment learning can improve student learning outcomes on the concept of the digestive system.